2015
DOI: 10.1039/c4ra14567d
|View full text |Cite
|
Sign up to set email alerts
|

A solution-processed high-efficiency p-NiO/n-ZnO heterojunction photodetector

Abstract: Solution-processed high-efficiency p–n heterojunction photodetectors have been developed using transition metal oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 48 publications
3
23
0
Order By: Relevance
“…Among the variety of p-type materials that have been employed to form p-n junction with ZnO, p-NiO stands out due to its band alignment with ZnO and its alloys in UV PD applications. 15, 17, 18 Although excellent figures of merits have been achieved in NiO/ZnO PDs, most of the devices have been fabricated on rigid substrates using high processing temperature without any self-powered behavior 16, 17 which can limit their application on plastic substrates. On the other hand, some devices have shown very slow temporal response 18 that may not be suitable for high-speed device applications.…”
mentioning
confidence: 99%
“…Among the variety of p-type materials that have been employed to form p-n junction with ZnO, p-NiO stands out due to its band alignment with ZnO and its alloys in UV PD applications. 15, 17, 18 Although excellent figures of merits have been achieved in NiO/ZnO PDs, most of the devices have been fabricated on rigid substrates using high processing temperature without any self-powered behavior 16, 17 which can limit their application on plastic substrates. On the other hand, some devices have shown very slow temporal response 18 that may not be suitable for high-speed device applications.…”
mentioning
confidence: 99%
“…Besides these significant developments, solution‐processed diodes based on chalcogenides . for photodetectors and all‐oxide diodes for solar cells and photodetector . applications have also been reported by various research groups.…”
Section: Beyond Single Fetsmentioning
confidence: 99%
“…There have already been a number of papers concerning the marrying of n-type ZnO with p-type NiO, particularly for LED [15,16] and photodetector [17,18] applications. Recently, it has been suggested that the adoption of such junctions might be extended to other third generation transparent electronics applications [19,20].…”
Section: Introductionmentioning
confidence: 99%